Analisis diskriminan faktor kecemasan karyawan menghadapi dampak Pandemi Covid-19: Kasus perusahaan manufacturing dan jasa survey - Setiawan San; Welly Atikno; Suratno Suratno (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
At the beginning of 2020 the world was shocked by the corona virus pandemic (Covid-19) which infected almost all countries in the world. In Indonesia this has an impact on the manufacturing industry sector and survey services. Through this phenomenon, researchers want to look at human psychological factors, how anxious they are about the impact of covid-19, which can lead to potential infection, reduced personal income, companies going bankrupt, massive layoffs, reduced need for staples, and communication between employees which is obstructed. The study design used a cross sectional approach by distributing questionnaires to 220 employees, from the manager, supervisor and staff level using the Discriminant analysis method so that the discriminant function to determine the level of anxiety evaluation was D = -0.003 + 0.634x1 + 0.696x3 - 0.520x4 + 0.168 x5 - 0.864x7.